Larger foraminiferal biostratigraphy of the Tethyan Paleocene and Eocene - J. Serra Kiel; L. Hottinger; E. Caus; K. Drobne; C. Ferrandez; A. K. Jauhri; G. Less; R. Pavlovec; J. M. Samso; H. Schaub; E. Sirel; A. Strougo; et al. (SOC GEOL FRANCE, 1998)
Abundance, diversity, and high evolutionary rates make larger foraminifera useful biostratigraphic tools for datation of sediments deposited in shallow marine platforms. Twenty shallow benthic zones (SBZ) are defined in the time span ranging from the base of Paleocene up to the Eocene-Oligocene boundary. A SBZ zone is characterized upon the stratigraphic distribution of several taxa, belonging mainly to alveolinids, nummulitids and orthophragminids. The correlation of shallow benthic zones with the Paleocene-Eocene Time Scale by Berggren et al. [1995] is proposed on the basis of magnetostratigraphic data from the Pyrenean Basin and by biostratigraphic correlation with the biozonations of calcareous nannoplankton and planktonic foraminifera in the eastern and central part of Tethys.